Studies in the theory of international trade - Viner, Jacob (London : Allen & Unwin, 1955)
The book examines some theories of international trade as a useful supplement. It also gives extensive discussions of early monetary and banking theories.
Includes index
Includes bibliographical references: pp. 602-631
usc 22/01/2019
Loans
Keywords: Commerce; International trade; Commercial policy; Economics